MONITORING THE QUALITY OF LIQUID FUELS USING SPECTROSCOPY METHODS – SELECTION OF A LIGHT SOURCE - Bożena SZCZUCKA-LASOTA; Tomasz WĘGRZYN; Feng CHEN; Katarzyna TUROŃ (Scientific Journal of Silesian University of Technology. Series Transport)
The aim of the article is to develop a new measurement station for assessing the quality of liquid fuels using light spectroscopy methods. Tests were carried out using various light sources, transmittance and absorbance were determined, and sources for liquid fuel tests were selected. Fuel samples were prepared. At the developed stand, it was checked whether the developed measurement method is suitable for determining the quality of liquid fuel. The novelty of the article is to show that spectroscopy methods using appropriate light sources are a prospective solution for determining the quality of liquid fuels during continuous monitoring. The research was performed in laboratory conditions. The technology requires development and adaptation to real conditions; the research conducted is qualitative and not quantitative.